Selenium content and bioaccumulation in Bidens tripartita and Bidens frondosa under different habitat conditions in Poland and Montenegro - Zuzanna Krzynówek; Edyta Stępień-Zawal; Zofia Sotek; Joanna Pakulnicka; Bogumiła Pilarczyk; Katarzyna Malinowska; Vesna Vukašinović-Pešić; Vladimir Pešić; Ewa Filip; Małgorzata Bąkowska; Renata Pilarczyk; Andrzej Zawal (Scientific Reports)
Abstract The subjects of this study were two congeneric species of the genus Bidens, the European native Bidens tripartita and the invasive Bidens frondosa. The aim of this research was to determine: (1) the selenium content of the specimens of these species and the soils in which they grew, (2) the role of habitat parameters in shaping selenium levels in the soil and the plants studied, and (3) the bioaccumulation potential of the plants studied, taking habitat conditions into account. Specimens of both species were collected from riverbanks in Poland and Montenegro, and the Se concentrations in each specimen and in the soil sample from each site were measured. Our studies indicate that the invasive species B. frondosa has significantly higher selenium concentrations and greater bioaccumulation abilities (BCF > 1) compared to B. tripartita. Despite the average selenium concentration in the soil being higher in Poland than in Montenegro, Se concentration accumulated in B. frondosa collected in Montenegro was higher, it was also observed that soil chemical properties affect Se bioaccumulation in this species. The type of land use within each site has also been identified according to CORINE classification. The results of the study indicated a great significance of human impact on the selenium enrichment of plants, as the specimen collected in artificial rivers and areas impacted by anthropogenic pression contained much higher amounts of Se than plants growing in more natural habitats. The results also illustrated that the invasive species that have the ability to accumulate selenium, like B. frondosa, can be an exogenous root of this particular trace element for living organizms.